The influence of a consumer-wearable activity tracker on sedentary time and prolonged sedentary bouts: Secondary analysis of a randomized controlled trial NCT01855776 NCT - Sloan, R.A. (BioMed Central Ltd., 2020)
10.1186/s13104-018-3306-9